HERA-GITRL activates T cells and promotes anti-tumor efficacy independent of FcγR-binding functionality. Issue 1 (19th July 2019) - Richards, David M.; Marschall, Viola; Billian-Frey, Katharina; Heinonen, Karl; Merz, Christian; Redondo Müller, Mauricio; Sefrin, Julian P.; Schröder, Matthias; Sykora, Jaromir; Fricke, Harald; Hill, Oliver; Gieffers, Christian; et al.
Abstract : Background: Glucocorticoid-induced TNFR-related protein (TNFRSF18, GITR, CD357), expressed by T cells, and its ligand (TNFSF18, GITRL), expressed by myeloid populations, provide co-stimulatory signals that boost T cell activity. Due to the important role that GITR plays in regulating immune functions, agonistic stimulation of GITR is a promising therapeutic concept. Multiple strategies to induce GITR signaling have been investigated. The limited clinical efficacy of antibody-based GITR agonists results from structural and functional characteristics of antibodies that are unsuitable for stimulating the well-defined trimeric members of the TNFRSF. Methods: To overcome limitations of antibody-based TNFRSF agonists, we have developed HERA-GITRL, a fully human hex avalent TNF r eceptor a gonist (HERA) targeting GITR and mimicking the natural signaling concept. HERA-GITRL is composed of a trivalent but single-chain GITRL-receptor-binding-domain (scGITRL-RBD) unit fused to an IgG1 derived silenced Fc-domain serving as dimerization scaffold. A specific mouse surrogate, mmHERA-GITRL, was also generated to examine in vivo activity in respective mouse tumor models. Results: For functional characterization of HERA-GITRL in vitro, human immune cells were isolated from healthy-donor blood and stimulated with anti-CD3 antibody in the presence of HERA-GITRL. Consistently, HERA-GITRL increased the activity of T cells, including proliferation and differentiation, even in the presence of regulatory T cells. In line with these findings, mmHERA-GITRL enhanced antigen-specific clonal expansion of both CD4+ (OT-II) and CD8+ (OT-I) T cells in vivo while having no effect on non-specific T cells. In addition, mmHERA-GITRL showed single-agent anti-tumor activity in two subcutaneous syngeneic colon cancer models (CT26wt and MC38-CEA). Importantly, this activity is independent of its FcγR-binding functionality, as both mmHERA-GITRL with a functional Fc- and a silenced Fc-domain showed similar tumor growth inhibition. Finally, in a direct in vitro comparison to a bivalent clinical benchmark anti-GITR antibody and a trivalent GITRL, only the hexavalent HERA-GITRL showed full biological activity independent of additional crosslinking. Conclusion: In this manuscript, we describe the development of HERA-GITRL, a true GITR agonist with a clearly defined mechanism of action. By clustering six receptor chains in a spatially well-defined manner, HERA-GITRL induces potent agonistic activity without being dependent on additional FcγR-mediated crosslinking.